Controlled release of fibrin matrix-conjugated platelet derived growth factor improves ischemic tissue regeneration by functional angiogenesis. (1st January 2016) - Mittermayr, Rainer; Slezak, Paul; Haffner, Nicolas; Smolen, Daniel; Hartinger, Joachim; Hofmann, Anna; Schense, Jason; Spazierer, Daniel; Gampfer, Jörg; Goppelt, Andreas; Redl, Heinz
Graphical abstract: Abstract: Sustained, local, low dose growth factor stimulus of target tissues/cells is believed to be of imminent importance in tissue regeneration and engineering. Recently, a technology was developed to bind growth factors to a fibrin matrix using the transglutaminase (TG) activity of factor XIIIa, thus allowing prolonged release through enzymatic cleavage. In this study we aimed to determine whether TG-PDGF.AB in fibrin could improve tissue regeneration in a standard ischemic flap model. In vitro determination of binding and release kinetics of TG-PDGF.AB allowed proof of concept of the developed binding technology. A single spray application of TG-PDGF.AB in fibrin matrix at a concentration of 10 and 100 ng/ml significantly reduced ischemia-induced flap tissue necrosis in vivo on day 7 after ischemic impact compared to controls. TG-PDGF.AB at a concentration of 100 ng/ml fibrin induced distinct angiogenesis as reflected by significantly improved tissue perfusion assessed by laser Doppler imaging as well as enhanced von Willebrand factor (vWF) protein expression determined by immunohistochemical means. In addition, significantly more mature microvessels were observed with 100 ng/ml TG-PDGF.AB in fibrin compared to control and vehicle groups as evidenced by an improved smooth muscle actin (sma)/vWF protein ratio. In conclusion, PDGF.AB in a conjugated fibrin matrix effectively reduced ischemia-induced tissue necrosis, increased tissue perfusion and induced the growth of a mature and functional neovasculature. The sealing properties of the fibrin matrix in conjunction with the prolonged growth factor stimulus enabled by the TG-hook binding technology may present an innovative and suitable tool in tissue regeneration. Statement of significance: In our experimental study we elucidated recombinant platelet derived growth factor (PDGF) as a potential candidate in inducing angiogenesis. To avoid preterm growth factor degradation in vivo PDGF.AB was covalently linked to a fibrin scaffold using a bi-domain functionalized peptide (FXIII substrate site and plasmin cleavage site). This allowed PDGF binding to fibrin during spray application to the donor site and subsequent prolonged release via endogenous plasmin. This resulted in a mature vascular network thus enhancing tissue perfusion and consequently improved clinical outcome. With our present work we could certainly provide researchers and clinicians with an innovative versatile and reproducible technology not only to induce functional vascularity but also to improve attempts in tissue engineering in general by e.g. using different growth factors. Hence, we believe that this approach studied in the present work may provide a valuable input in an effort to drive the aim forward bringing experimental work in tissue engineering to clinic by using a clinically well characterized and used fibrin scaffold in combination with a human recombinant growth factor (fibrin scaffold linked with the specific binding technology).